Role of 18-Fluorine Fluoro-deoxy Glucose Positron Emission Tomography (FDG-PET/CT scan) in Suspected Relapsed Ovarian Cancer; an Institutional Experience. - Wahab, Abdul; Hanif, Muhammad Rashid; Riaz, Saima; Khan, Shafquat Ali; Azhar, Musa; Siddiqui, Neelam (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To determine the role of 18-Fluorine Fluoro-deoxy glucose Positron Emission Tomography (18F FDG-PET/CT scan) in suspected relapsed ovarian cancer patients. Study Design: Cross-sectional study. Place and Duration of Study: Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore Pakistan, from Jan 2010 to Dec 2017. Methodology: A total of 964 patients of epithelial ovarian carcinoma who had histologically proven ovarian cancer diagnosed from January 2010 until December 2017 were reviewed. 70 patients on surveillance who had FDG-PET/CT scan for suspected relapse were included in our study. Data collected from the digital Hospital Information System after Institutional review board approval. Results: Average age for our study group was 48.6 years ± 11.4 SD. Serous pathology was predominant in 47/70(67.1%) patients followed by Endometroid (14.3%). FDG-PET/CT scan changed the stage in 30% patients. Sensitivity, specificity, positive predictive value, and negative predictive value of FDG-PET/CT were 96%, 72%, 89% and 88% respectively while it is 92%, 76%, 90%, and 80% respectively for conventional CT scan. Average Cancer antigen-125 (CA-125) at suspected relapse is 290. 21 patients (75%) showed FDG avid disease on PET scan in whom CA-125 was normal. Conclusion: PET scan has better negative predictive value than conventional CT scan to detect relapse in ovarian cancer, its overall sensitivity is comparable to contrast-enhanced CT scan. CA-125 is not a reliable marker for the detection of relapse in ovarian cancer patients.